2021
DOI: 10.1016/j.jhep.2021.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Bile formation and secretion: An update

Abstract: Bile formation is a fundamental physiological process that is vital to the survival of all vertebrates. However, little was known about the mechanisms of this secretion until after World War II. Initial studies involved classic physiologic studies in animal models and humans, which progressed to include studies in isolated cells and membrane vesicles. The advent of molecular biology then led to the identification of specific transport systems that are the determinants of this secretion. Progress in this field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 101 publications
0
45
0
Order By: Relevance
“…ABCB1 absorbs and transfers out of the cells the exogenous substances that enter the body and the harmful toxins produced by the body's metabolism. The transporter MDR1 located at the top of the bile capillary is the determinant of bile secretion and composition, and its main function is to transport hydrophobic compounds into the bile (Boyer and Soroka, 2021). In addition, some studies have shown that MDR1 promoted the excretion of bilirubin and bile acid, and accelerated the efflux of hepatotoxic substances, so as to dispel jaundice, cholagogic and detoxification, thereby regulating bile acid metabolism (Tang et al, 2016;Jetter and Kullak-Ublick, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…ABCB1 absorbs and transfers out of the cells the exogenous substances that enter the body and the harmful toxins produced by the body's metabolism. The transporter MDR1 located at the top of the bile capillary is the determinant of bile secretion and composition, and its main function is to transport hydrophobic compounds into the bile (Boyer and Soroka, 2021). In addition, some studies have shown that MDR1 promoted the excretion of bilirubin and bile acid, and accelerated the efflux of hepatotoxic substances, so as to dispel jaundice, cholagogic and detoxification, thereby regulating bile acid metabolism (Tang et al, 2016;Jetter and Kullak-Ublick, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…After food ingestion, the gallbladder releases these BAs into the duodenum, where they function in the small intestine and colon. After the BAs assist in the digestion of food, most are reabsorbed back into the liver in a process known as the enterohepatic circulation of BAs ( 45 ). A number of recent studies have found that unabsorbed BAs in the intestine can be used as substrates for microbial metabolism and further transformed into secondary BAs through hydrolase or dehydrogenase enzymes.…”
Section: Gut Microbiota and Metabolitesmentioning
confidence: 99%
“…These intestinal bacteria are mainly composed of Lactobacillus, Streptococcus, Enterobacter, Enterococcus, Clostridium, Lactobacillus, Veronococcus ( 46 ). They separate BAs from glycine or taurine to form mainly deoxycholic acid (DCA) and lithocholic acid (LCA), which in turn, may be further recirculated to the liver and, like primary BAs, combine with glycine or taurine and are excreted in small amounts in the feces ( 45 ).…”
Section: Gut Microbiota and Metabolitesmentioning
confidence: 99%
“…It may also contain exogenous drugs, xenobiotics and environmental toxins [3]. Bile is first secreted by the hepatocyte into the canalicular lumen, where biliary flow is aided by transcellular and paracellular fluid movement as well as peristaltic actin contractions [4]. This bile is then modified by secretory and absorptive processes in the bile duct epithelium as it flows distally through the bile ducts.…”
Section: Normal Bile Secretion and Flowmentioning
confidence: 99%